1994
DOI: 10.1002/mds.870090406
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of dyskinesias in advanced Parkinson's disease: Moderate daily clozapine doses provide long‐term dyskinesia reduction

Abstract: Dyskinesias commonly appear during L-dihydroxyphenylalanine (L-DOPA) therapy of advanced Parkinson's disease (PD) and can occur in both dose-related and dose-independent patterns. Clozapine exerts a dose-related suppression of L-DOPA-induced dyskinesias by shifting the i.v. L-DOPA dose-response curve for production of dyskinesias without altering relief of parkinsonism. We report our outpatient experience with 13 patients on daily clozapine therapy (maximum dose 400 mg/day), followed for 3-21 months (median 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(37 citation statements)
references
References 20 publications
1
36
0
Order By: Relevance
“…The efficacy of clozapine, a DA receptor antagonist with 5673 antiserotonergic, antimuscarinic, antiadrenergic and antihistami-5674 nergic properties, in decreasing LID was evaluated in several small pilot studies (Bennett et al, 1993(Bennett et al, , 1994Durif et al, 1997;Pierelli 5676 et al, 1998) and in one larger randomized, placebo controlled trial 5677 (Durif et al, 2004). In the latter, patients treated with clozapine 5678 gained 2.4 h of ON time without dyskinesia compared to placebo.…”
mentioning
confidence: 99%
“…The efficacy of clozapine, a DA receptor antagonist with 5673 antiserotonergic, antimuscarinic, antiadrenergic and antihistami-5674 nergic properties, in decreasing LID was evaluated in several small pilot studies (Bennett et al, 1993(Bennett et al, , 1994Durif et al, 1997;Pierelli 5676 et al, 1998) and in one larger randomized, placebo controlled trial 5677 (Durif et al, 2004). In the latter, patients treated with clozapine 5678 gained 2.4 h of ON time without dyskinesia compared to placebo.…”
mentioning
confidence: 99%
“…90 Bennett et al suggested that clozapine is effective in suppressing dyskinesias in PD by increasing the threshold for dyskinesias associated with levodopa treatment, with the effective daily dose for most patients being 100-200 mg/day. 91 More recently, in a double-blind placebo-controlled study, Durif et al also reported the efficacy of clozapine in the treatment of levodopainduced dyskinesias in severe PD. 92 Other studies have reported that a low dose of clozapine is beneficial in treating levodopa-induced dyskinesias.…”
Section: Second-generation Antipsychotics (Serotonindopamine Antagonimentioning
confidence: 97%
“…In another open-label study, 13 patients with PD were treated with clozapine (maximum dose of 400 mg/d) and prospectively evaluated for 3 to 21 months (median of 10 months) [51]. Patients kept bi-weekly diaries to assess motor function throughout the study.…”
Section: Clozapinementioning
confidence: 99%